Changes in degranulation and histamine release from mast cells in rats sensitized by penicilloyl-protein - Zhao Zhen-jun; Ma Tong-xun (Acta Pharmacologica Sinica, 2016)
In this paper, the mechanism of the penicillin G anaphylactic reaction was studied. Rats were sensitized to penicilloyl (BPO)-protein. The incidences of anaphylactic reaction and death were 100 and 40%, respectively. After being challenged, the degranulation rates of rat cranial periosteous and peritoneal mast cells were 91 +/- 5 and 44 +/- 10%, respectively. In the control group, they were 11 +/- 5 and 7 +/- 2%, respectively. The histamine release rates from sensitized and control rat peritoneal mast cells were 13 +/- 2 and 3.0 +/- 0.4%, respectively. The passive cutaneous anaphylaxis (PCA) test demonstrated that the antibody titers in sensitized serum were 16-32.